Sinus Microanatomy and Microbiota in a Rabbit Model of Rhinosinusitis - Cho, Do-Yeon; Mackey, Calvin; Van Der Pol, William J.; Skinner, Daniel; Morrow, Casey D.; Schoeb, Trenton R.; Rowe, Steven M.; Swords, William E.; Tearney, Guillermo J.; Woodworth, Bradford A. (Frontiers in Cellular and Infection Microbiology, 2018)
Background: Rabbits are useful for preclinical studies of sinusitis because of similar physiologic features to humans. The objective of this study is to develop a rabbit model of sinusitis that permits assessment of microanatomy and sampling for evaluating shifts in the sinus microbiota during the development of sinusitis and to test how the mucociliary clearance (MCC) defect might lead to dysbiosis and chronic rhinosinusitis (CRS). Methods: Generation of CRS was accomplished with an insertion of a sterile sponge into the left middle meatus of New Zealand white rabbits (n = 9) for 2 weeks. After sponge removal, 4 rabbits were observed for another 10 weeks and evaluated for CRS using endoscopy, microCT, visualization of the functional micro-anatomy by micro-optical coherence tomography (μOCT), and histopathological analysis of the sinus mucosa. Samples were taken from the left middle meatus and submitted for microbiome analysis. Results: CT demonstrated opacification of all left sinuses at 2 weeks in all rabbits (n = 9), which persisted in animals followed for another 12 weeks (n = 4). Histology at week 2 showed mostly neutrophils. On week 14, significant infiltration of plasma cells and lymphocytes was noted with increased submucosal glands compared to controls (p = 0.02). Functional microanatomy at 2 weeks showed diminished periciliary layer (PCL) depth (p < 0.0001) and mucus transport (p = 0.0044) compared to controls despite a thick mucus layer. By 12 weeks, the thickened mucus layer was resolved but PCL depletion persisted in addition to decreased ciliary beat frequency (p < 0.0001). The mucin fermenting microbes (Lactobacillales, Bacteroidales) dominated on week 2 and there was a significant shift to potential pathogens (e.g. Pseudomonas, Burkholderia) by week 14 compared to both controls and the acute phase (p< 0.05). Conclusion: We anticipate this reproducible model will provide a means for identifying underlying mechanisms of airway-surface liquid (ASL) depletion and fundamental changes in sinus microbial communities that contribute to the development of CRS. The rabbit model of sinusitis exhibited diminished PCL depth with delayed mucus transport and significant alterations and shift in the sinus microbiome during the development of chronic inflammation.